Microbial biocompatibility of phosphonium- and ammonium-based ionic liquids - Sivapragasam, M. (2019)
This present study is dedicated to the synthesis, characterization and microbial toxicity assessment of phosphonium- and ammonium-based ionic liquids (ILs) bearing four different anions phenylalalinate (Phe), taurinate (Tau), hydroxide (OH), and acetate (Ac). The structures of the subsequent ILs were confirmed by 1H and 13C nuclear magnetic resonance (NMR). Physicochemical properties such as density, thermal stability, conductivity, surface tension, and refractive index were measured. Subsequently, the in vitro toxicity profiles of the ILs were determined for selected Gram-positive and Gram-negative bacteria in terms of inhibition zones (IZ), minimum inhibitory concentrations (MIC), and minimum bactericidal concentrations (MBC). The results showed that the ILs were in the range of âpractically harmlessâ to âharmlessâ. The order of the same was OH > Ac > Tau > Phe, with phenylalalinate being the most toxic anion owing to its aromatic nature. With reference to the experimental results, the nature of the critical micellar concentrations and water octanol partitioning was discussed in the context of microbial toxicity. Hence, it was shown that anions, rather than cations, were the major contributors to toxicity. Â© 2018 Elsevier B.V.